1993
DOI: 10.1159/000216852
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Fragment 1+2 and Thrombin-Antithrombin Complex Measurements Indicate Continuous and Progressive Intraoperative Thrombin Generation in Liver Transplantation

Abstract: Prothrombin fragment 1 + 2 (F1+2) and thrombin-antithrom-bin complex (TAT) have been measured in the different surgical phases in 40 patients undergoing 43 orthotopic liver transplantations (OLT), in order to study thrombin generation throughout the surgical procedure. F1+2 and TAT progressively rose from preoperative values (1.47 ± 0.92 nmol/l and 22.41 ± 19.15 ng/ml, respectively) to the end of anhepatic phase (5.97 ± 2.20 nmol/l, 64.24 ± 11.30 ng/ml), whereas changes in circulating ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Those with more severe HLE may have greater inhibition of thrombin generation as they have greater antithrombin III binding. A previous study investigating thrombin‐antithrombin complexes during liver transplantation showed thrombin generation to slightly increase after reperfusion 23. However, this study did not investigate those with HLE separately.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Those with more severe HLE may have greater inhibition of thrombin generation as they have greater antithrombin III binding. A previous study investigating thrombin‐antithrombin complexes during liver transplantation showed thrombin generation to slightly increase after reperfusion 23. However, this study did not investigate those with HLE separately.…”
Section: Discussionmentioning
confidence: 91%
“…Heparin acts by binding with anti‐thrombin III inhibiting thrombin generation 22. When given to patients, it demonstrates significant interindividual variability23 and behaves in a dose‐dependent linear model with saturable pharmacokinetics 22. Those with more severe HLE may have greater inhibition of thrombin generation as they have greater antithrombin III binding.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was separated by centrifugation of the anticoagulated blood samples (1800 × g for 20 min) and frozen at –70°C. Levels of F1 + 2 were determined in plasma samples with commercially available EIAs (Enzygnost, Behring, Germany) 30 …”
Section: Methodsmentioning
confidence: 99%
“…Levels of F1 + 2 were determined in plasma samples with commercially available EIAs (Enzygnost, Behring, Germany). 30 blood, and with antibodies against TF for each concentration and controls were at least n = 6. Experiments with blood from Glanzmann's thrombastenia patients were performed with blood samples taken from two different patients (n = 2) and experimental studies with blood samples exposed to a specific MoAb against GPIIb-IIIa was n = 4.…”
Section: Evaluation Of Thrombin Generationmentioning
confidence: 99%
“…Blood aliquots were immediately mixed with sodium citrate (129 m M ) to prevent further activation of the coagulation system. Plasma was separated by centrifugation of the anticoagulated blood samples (1800 × g , 20 min) and frozen at –70 C. F1+2 levels were determined by commercially available EIAs (Enzygnost F1+2, Dade Behring, Marburg, Germany) according to the method already described 29 …”
Section: Methodsmentioning
confidence: 99%